2007
DOI: 10.4049/jimmunol.178.6.3731
|View full text |Cite
|
Sign up to set email alerts
|

TLR4-Mediated Survival of Macrophages Is MyD88 Dependent and Requires TNF-α Autocrine Signalling

Abstract: Modulation of macrophage survival is a critical factor in the resolution of inflammatory responses. Exposure to LPS protects innate immune cells against apoptosis, although the precise pathways responsible for prolongation of macrophage survival remain to be fully established. The goal of this study was to characterize the mechanism of TLR4-mediated survival of murine bone marrow-derived macrophages upon M-CSF withdrawal in more detail. Using a combination of knockout mice and pharmacological inhibitors allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 52 publications
(47 reference statements)
10
75
0
1
Order By: Relevance
“…Although it has been reported that TNF has a prosurvival effect on monocyte/macrophages in vitro (71,72), the issue of whether TNF neutralization can lead to apoptosis in tissue macrophages and/or blood monocytes has been debated. The divergent observations are probably due to the variety of conditions under which the studies were carried out (2,(73)(74)(75).…”
Section: Cytokine Blockade Tnf Il-1 and Il-6mentioning
confidence: 99%
“…Although it has been reported that TNF has a prosurvival effect on monocyte/macrophages in vitro (71,72), the issue of whether TNF neutralization can lead to apoptosis in tissue macrophages and/or blood monocytes has been debated. The divergent observations are probably due to the variety of conditions under which the studies were carried out (2,(73)(74)(75).…”
Section: Cytokine Blockade Tnf Il-1 and Il-6mentioning
confidence: 99%
“…TLR4 has been linked to both parallel proapoptotic and survival pathways. LPS induces apoptosis in endothelial cells (27) and hepatocytes (49), whereas it has an antiapoptotic effect in monocytes (44,94), neutrophils (156), macrophages (90), and cardiomyocytes (26,170). In the cells protected by LPS treatment, the activation of TLR4 triggers the expression of cell survival and inflammatory genes via NF-B-dependent mechanisms.…”
Section: Tlr Signaling Modulates Cardiomyocyte Apoptosismentioning
confidence: 99%
“…However, using a genetically engineered mice (MyD88 Ϫ/Ϫ ) and in an acute lung injury model, Jiang et al (68) have recently demonstrated that MyD88 mediates an antiapoptotic signal in lung epithelial cells and plays a critical role in pulmonary tissue repair and inflammation during the bleomycin-induced lung injury. Similarly, MyD88 appears essential for TLR4-activated antiapoptotic signaling in mouse cardiomyocytes (170) and in macrophages (90). Moreover, the adenovirus-mediated expression of MyD88 modulates TLR2-induced cytokine production in mouse cardiomyocytes (169) but is not sufficient to affect cardiomyocyte apoptosis in vitro.…”
Section: Tlr Signaling Modulates Cardiomyocyte Apoptosismentioning
confidence: 99%
“…Whereas most studies suggest that lipoproteins do induce apoptosis [3436], others report that lipoproteins in fact have anti-apoptotic properties [37]. The observed anti-apoptotic effects could be due to the lipoprotein-stimulated production of TNF-α, as indicated by the finding that LPS-induced long-term survival of macrophages depended on TNF-α autocrine signalling [38]. However, in addition to the fact that the induction of pro- or anti-apoptotic pathways is multi-factorially regulated, the experimental conditions, such as differences in lipoprotein structures, types of cells used and culture conditions likely play a role [38], which may lead to conflicting results in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The observed anti-apoptotic effects could be due to the lipoprotein-stimulated production of TNF-α, as indicated by the finding that LPS-induced long-term survival of macrophages depended on TNF-α autocrine signalling [38]. However, in addition to the fact that the induction of pro- or anti-apoptotic pathways is multi-factorially regulated, the experimental conditions, such as differences in lipoprotein structures, types of cells used and culture conditions likely play a role [38], which may lead to conflicting results in different studies. The used AaPAL preparation was highly pure, the only contaminants being low amounts of LPS and BSA [28]; thus, we trusted that the observed effects were caused by AaPAL.…”
Section: Discussionmentioning
confidence: 99%